RISKS OF EURASIAN INTEGRATION - Onishchenko, Volodymyr (Journal of European Economy, 2017)
The basic political, institutional and economic risks while creation of the Eurasian Economic Union and their possible impact on its stability and efficiency of development is proved; the author’s position regarding the impossibility of the long-term socio-economic effects for the members of the Union is grounded; the probable risks for Russia as the leader of the integration process which prevent the Eurasian integration are identified.